Supraphysiological Triiodothyronine Doses Diminish Leptin and Adiponectin Gene Expression, but do not Alter Resistin Expression in Calorie Restricted Obese Rats - Luvizotto, R. A. M. [UNESP]; Sibio, M. T. [UNESP]; Olimpio, R. M. C. [UNESP]; Nascimento, A. F. [UNESP]; Lima-Leopoldo, A. P.; Leopoldo, A. S. [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP]; Nogueira, Célia Regina [UNESP] (Georg Thieme Verlag Kg, 2011)
Thyroid hormones regulate energy balance and act on adipokines. However, while it is unclear what the effects are of calorie restriction and high doses of triiodothyronine (T(3)) on adipokines in obesity, thyroid hormones are illicitly administered in isolation or in association with a hypocaloric diet as an obesity treatment. The present study determined the effect of T(3) on serum concentrations and gene expression of the adipokines leptin, resistin, and adiponectin in calorie-restricted obese rats. Male Wistar rats received a hypercaloric diet for 20 weeks followed by calorie restriction for 8 weeks. The animals were then randomly divided into 3 groups: calorie restriction (OR), OR with 5 mu g of T(3)/100g BW (RS1), and OR with 25 mu g of T(3)/100g BW (RS2) for 2 weeks. Blood and adipose tissue samples were collected for biochemical, hormonal, and gene expression analyses. Serum concentrations of leptin (OR: 3.7 +/- 0.6, RS1: 3.8 +/- 1, RS2 0.2 +/- 0.07 ng/dl) and resistin (OR: 2.5 +/- 0.6, RS1: 2.5 +/- 0.5, RS2 1.6 +/- 0.3 ng/dl) were diminished at the higher dose, while serum adiponectin (OR: 31 +/- 7, RS1: 24 +/- 5, RS2 26 +/- 7 ng/dl) levels were lower in the low dose group. Administration of T(3) reduced leptin gene expression (OR: 0.91 +/- 0.1, RS1: 0.95 +/- 0.1, RS2 0.22 +/- 0.1) only at the higher dose, resistin expression (OR: 1.06 +/- 0.2, RS1: 1.04 +/- 0.1, RS2 0.88 +/- 0.2) was not influenced by T(3) treatment, and adiponectin expression (OR: 1.55 +/- 0.5, RS1: 0.95 +/- 0.15, RS2 0.97 +/- 0.13) was diminished independent of the T(3) dose. These results indicate that T(3), directly or indirectly, inhibits the expression of leptin and adiponectin in calorie restricted obese animals.
Keywords: thyroid hormone; adipose tissue; high-fat diet; food deprivation